2022
DOI: 10.1038/s41467-022-34145-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling reveals distinct adaptive immune hallmarks in MDA5+ dermatomyositis with therapeutic implications

Abstract: Anti-melanoma differentiation-associated gene 5-positive dermatomyositis (MDA5+ DM) is an autoimmune condition associated with rapidly progressive interstitial lung disease and high mortality. The aetiology and pathogenesis of MDA5+ DM are still largely unknown. Here we describe the immune signatures of MDA5+ DM via single-cell RNA sequencing, flow cytometry and multiplex immunohistochemistry in peripheral B and T cells and in affected lung tissue samples from one patient. We find strong peripheral antibody-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 83 publications
2
31
0
Order By: Relevance
“…The activation of type I IFN signaling in JDM blood and target tissues has been reported in many previous studies (Wenzel et al, 2006;Baechler et al, 2007;Bilgic et al, 2009;Baechler et al, 2011;Wong et al, 2012;Neely et al, 2019;Soponkanaporn et al, 2019;Neely et al, 2022), and has been identified as a predominant feature in MDA5 + DM patients that is related to endothelial injury (Funauchi et al, 2006;He et al, 2021), vasculopathy (Ono et al, 2019;Cassius et al, 2020), and lung injury (Nakano et al, 2012;Takada et al, 2015;Ye et al, 2022). Type I IFN plays essential role in establishing and modulating host immune response to the complex pathogenic or environmental stimuli via induction of IFNstimulated genes (ISGs) through Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, and the dysregulation of type I IFN production and function could induce an inflammatory state in patients by aberrantly activating inflammatory responses or improperly suppressing microbial controls (Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The activation of type I IFN signaling in JDM blood and target tissues has been reported in many previous studies (Wenzel et al, 2006;Baechler et al, 2007;Bilgic et al, 2009;Baechler et al, 2011;Wong et al, 2012;Neely et al, 2019;Soponkanaporn et al, 2019;Neely et al, 2022), and has been identified as a predominant feature in MDA5 + DM patients that is related to endothelial injury (Funauchi et al, 2006;He et al, 2021), vasculopathy (Ono et al, 2019;Cassius et al, 2020), and lung injury (Nakano et al, 2012;Takada et al, 2015;Ye et al, 2022). Type I IFN plays essential role in establishing and modulating host immune response to the complex pathogenic or environmental stimuli via induction of IFNstimulated genes (ISGs) through Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, and the dysregulation of type I IFN production and function could induce an inflammatory state in patients by aberrantly activating inflammatory responses or improperly suppressing microbial controls (Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 75%
“…Considering that type I IFNs play critical roles in innate immune responses regulating the antiviral responses, there is no doubt that ISG15 and its conjugation to target proteins play critical roles in the type I IFN-induced immune responses. Notably, type I IFN has been reported to promote CD8 + T-cell expansion ( Kolumam et al, 2005 ), while ISG15+ CD8 + T-cells may represent a promising prognostic biomarker in MDA5 + DM ( Ye et al, 2022 ). In this study, we also observed the expansion of CD8 + T-cells in untreated patients with JDM, further confirming that ISG15+ CD8 + T-cells might represent prognostic biomarker for JDM.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of interstitial lung disease, particularly rapidly progressive interstitial lung disease, poses significant obstacles to the prognosis of patients with anti-MDA5+ DM. Overactivation of the type I IFN pathway is apparent in the affected lungs of patients with anti-MDA5+ DM according to a previous study (16). Type I IFN recruits CX3CR1+ M2 macrophages in the lungs by inducing the secretion of CX3CL (44,45), and M2 macrophages are responsible for producing tumor growth factor-b to promote pulmonary fibrosis (46)(47)(48).…”
Section: Discussionmentioning
confidence: 82%
“…Multiple markers are associated with the prognosis of anti-MDA5+ DM, including anti-MDA5 titers (41,42), the presence of anti-Ro52 antibody (43), lactate dehydrogenase (18), ferritin (5,24,26), KL-6 (27), the proportion of CD4+ CXCR4+ T cells (28), and a high proportion of ISG15+ CD8+ T cells (16). The presence of interstitial lung disease, particularly rapidly progressive interstitial lung disease, poses significant obstacles to the prognosis of patients with anti-MDA5+ DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation